A comparative performance evaluation of 12 HIV-1 viral load testing asssays: advancing the clinical application of HIV-1 nucleic acid testing in China - Yu Wang; Pinliang Pan; Wenge Xing; Xin Zhang; Boxue Han; Cong Jin (Microbiology Spectrum)
ABSTRACT HIV-1 viral load testing serves as a critical tool for monitoring antiretroviral therapy efficacy and detecting acute HIV-1 infections. This study evaluated the precision, linearity, and clinical performance of 12 commonly used HIV-1 viral load testing kits in China (including seven domestic and five imported kits). Precision analysis revealed that 11 kits achieved intra-assay coefficients of variation (CV%) below 5% for high and medium concentration standards at 10,000 and 1,000 IU/mL, respectively, while only 4 kits maintained comparable precision at low concentration standards (100 IU/mL). All kits showed excellent linear performance across their dynamic ranges (R² = 0.9924–0.9999) and effectively covered the major HIV-1 subtypes circulating in China. Correlation analysis of clinical samples showed strong associations (R² >0.70) in 49 out of 66 kit-pair comparisons, with Bland-Altman agreement analysis confirming good consistency between different kits. Notably, domestic Kit B exhibited minimal deviation (0.004 log10 IU/mL) compared to leading imported assays. Point-of-care testing kits demonstrated performance comparable to laboratory-based systems. However, observed variability in low viral load quantification highlights the need for improved precision to meet stringent clinical requirements for viral suppression monitoring at 50 copies/mL. These findings validate the reliability of domestic kits for clinical application while suggesting further enhancement in low-level viremia detection capabilities.IMPORTANCEHIV-1 viral load (VL) testing is extremely important in monitoring the efficacy of antiretroviral therapy and diagnosing acute HIV-1 infections. In China, the growing demand for nucleic acid testing (NAT) and rapid development of HIV-1 NAT technology have led to the approval of 15 HIV-1 VL kits by 2024, but their performance remains understudied. This study comprehensively evaluates 12 widely used HIV-1 VL kits (seven domestic and five imported) in China, demonstrating high precision, linearity, and clinical accuracy across prevalent HIV-1 subtypes in China. Notably, domestic kits exhibited a strong correlation with imported kits, validating their reliability for clinical use. However, variability in low VL quantification highlights challenges in meeting the stringent suppression threshold of 50 copies/mL. These findings provide evidence for optimizing HIV-1 NAT strategies, supporting the adoption of cost-effective domestic kits, and guiding future improvements for low-level viremia monitoring.